Using the Color Vowel Chart in Teaching Speaking - Syaifullah Syaifullah; Yulia Qoirum; Refika Andriani; Herlinawati Herlinawati (Universitas Lancang Kuning, 2022)
Abstract: Language is not only used for daily conversation, but also is used in education, research, and science both written and spoken. There are four basic skills in learning English should be mastered by students such as speaking, listening, reading and writing. To support all of four skills students should master speaking. One of the ways in improving speaking skill is through the Color Vowel Chart use. The aims of this study are divided into two; first, exploring information about the Color Vowel Chart, the techniques/strategies, the ways/procedures, and the assessment used in implementing the Color Vowel Chart in teaching speaking, second, investigating information in terms of students’ speaking achievement. This research is a qualitative study that uses theses, articles/journals and other literature as the main data sources where research that produces information in the form of notes and descriptive data contained in the text under study. The approach used in this research is a qualitative approach with descriptive method. The findings show that the students can increase their speaking skill by using the Color Vowel Chart. This happens because the success of using Color Vowel Chart in teaching speaking in is determined by some factors such as the media, the techniques/strategies, the ways/procedures, and the assessment used in implementing the Color Vowel Chart in teaching speaking. It proves by the results of the previous researchers’ studies. The previous researchers also used the Color Vowel Chart, techniques/strategies, ways/procedures, and the assessment. Fortunately, students can improve their speaking skill by the Color Vowel Chart. Key Words: Color Vowel Chart, Teaching, Speaking